Transform coding of DCT coefficients in video encoder - WANG Zhong-yuan; HU Rui-min; TIAN Gang; LI Ming (Tongxin xuebao)
The redundancy among discrete cosine transform（DCT） coefficients in video encoder was found very strong,a method for subband decomposition and transform coding was proposed.Each 8×8 DCT spectrum date of macroblock was regrouped to gather the same frequency bands.The Hadamard transform function was used and orthogonal integer Ha-damard transform formula was derived.Simulation results shows that the proposed approach reduces the spectrum redun-dancy and improves the compression efficiency further compared with conventional DCT coder,however the PSNR loss are almost invisible.This work is expected to contribute to the under drafted international video compression standard H.265.